From Face-to-Face to Virtual Mode Because of Covid-19: Impact in the Teaching-Learning Process - Chanto Espinoza, Carlos L. (2021)
Introduction: Within the framework of the pandemic provoked by the COVID-19, every teacher took the challenge to rebrand quickly and start working differently by designing and learning evaluative activities to face this E-Learning environment in which most students and teachers all around the world have been immersed for so long. Objective: To establish the impact of the methodological change within the traditional and virtual classroom in academics of Universidad Nacional of Costa Rica - Campus Liberia. Method: A total of 85 professors of the different majors have participated in this study and under a non-probabilistic sampling. A structured and closed questionnaire containing few questions was sent by e-mail utilizing the mail institutional platform and cellphones by the common digital platform WhatsApp. Results: The improvement of the pedagogic practice has a closed relationship with the good access to technologies and internet connection, which has been considered a clear limitation for academics to communicate with students in an easy, better and effective way. Discussion: The academy needs to have the clarity in relation to the conditions that students face daily in order to study utilizing distant education spaces which in many of the cases do not have access to the technological tools and connectivity, most of that due to their bad social and economic conditions.